Disrupsi ChatGPT dan Otoritas Keilmuan Pendidikan Islam: Sebuah Analisis Epistemologis - Abd Wahid; Jumriani; Irwani Lisaw (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2026)
Digital disruption has affected the construction of knowledge in education, including Islamic education. Not only as a means of facilitating learning, but it can also influence the way students learn, validate, and legitimize knowledge as a stand-alone epistemic authority. The purpose of this study is epistemological, which aims to investigate the impact of the use of ChatGPT on the authority of knowledge in Islamic education with a focus on the validity of knowledge, sanad, the role of teachers, and the emergence of algorithmic epistemic authority. This study uses qualitative research methods with the design of systematic literature review (SLR), PRISMA, thematic content analysis, and hermeneutic-critical analysis based on Islamic epistemology. Data collection was conducted from primary literature related to epistemology and current scientific articles related to ChatGPT in the field of Education. According to the results of the study, ChatGPT has successfully obtained algorithmic epistemic authority, which is based on its ability to respond quickly, linguistically, and comprehensively, without being tied to ulama in the Quran, its lack of moral authority, and its failure to hold any epistemic responsibility in Islamic epistemology. Thus, ChatGPT will never be able to become a teacher as murabbi, muaddib, and the keeper of scientific isnaad. The position of ChatGPT in Islamic education should not be as Marji'iyyah (as the main reference authority), but as wasilah (with a Supporting Role). The main problem of AI in Islamic education is not only the technical problem of using technology, but also the repositioning of knowledge authority in the era of digital transformation.